Ответ: x = 3.
Пошаговое объяснение:
[tex]2^{2x-7} =4,5 \cdot 9^{2x-7}\\2^{2x-7} =4,5 \cdot (4,5 \cdot 2)^{2x-7}\\2^{2x-7} =4,5 \cdot 4,5^{2x-7} \cdot 2^{2x-7}\\1=4,5 \cdot 4,5^{2x-7}\\1=4,5^{1+2x-7} \\1+2x-7=0\\2x-6=0\\2x=6\\x=3[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ: x = 3.
Пошаговое объяснение:
[tex]2^{2x-7} =4,5 \cdot 9^{2x-7}\\2^{2x-7} =4,5 \cdot (4,5 \cdot 2)^{2x-7}\\2^{2x-7} =4,5 \cdot 4,5^{2x-7} \cdot 2^{2x-7}\\1=4,5 \cdot 4,5^{2x-7}\\1=4,5^{1+2x-7} \\1+2x-7=0\\2x-6=0\\2x=6\\x=3[/tex]